Anti‐KIT antibody, barzolvolimab, reduces skin mast cells and disease activity in chronic inducible urticaria. Issue 5 (3rd December 2022) - Terhorst‐Molawi, Dorothea; Hawro, Tomasz; Grekowitz, Eva; Kiefer, Lea; Merchant, Kunal; Alvarado, Diego; Thomas, Lawrence J.; Hawthorne, Thomas; Crowley, Elizabeth; Heath‐Chiozzi, Margo; Metz, Martin; Maurer, Marcus
Abstract: Background: Chronic inducible urticaria (CIndU) is characterized by mast cell (MC)‐mediated wheals in response to triggers: cold in cold urticaria (ColdU) and friction in symptomatic dermographism (SD). KIT receptor activation by stem cell factor (SCF) is essential for MC function. Barzolvolimab (CDX‐0159) is a humanized antibody that inhibits KIT activation by SCF and was well tolerated in healthy volunteers with dose‐dependent plasma tryptase suppression indicative of systemic mast cell ablation. Methods: This is an open‐label, trial in patients with antihistamine refractory ColdU or SD, receiving one IV dose of barzolvolimab (3 mg/kg), with a 12‐week follow‐up. Primary endpoint was safety/tolerability; pharmacodynamic (PD)/clinical endpoints included serum tryptase, plasma SCF, skin MC histology, provocation tests, urticaria control test (UCT), and dermatology life quality index (DLQI). Results: Analysis populations were safety ( n = 21) and pharmacodynamics/clinical activity ( n = 20). Barzolvolimab was well tolerated; most adverse events were mild and resolved. Treatment resulted in significant depletion of skin MCs, decreased tryptase (<limit of detection), and increased soluble SCF through Week 12. Complete responses (negative provocation test) occurred in 95% ( n = 19/20) of patients ( n = 10/10 ColdU; n = 9/10 SD), and all ( n = 20/20) showed improvement in urticaria control (UCT ≥ 12). The kinetics of clinical activity mirrored that of MC and tryptase reduction. DLQI‐measured impairment significantly decreased to minimal/none in 93% of patients on study. Conclusion: In CIndU patients, barzolvolimab was well tolerated, demonstrated marked, rapid, durable depletion of skin MCs, circulating tryptase, and reductions in clinical activity with significant improvements in disease control and quality of life (QoL) demonstrating potential therapeutic effects for MC‐mediated disorders. Abstract : In this Phase 1b study of CIndU (ColdU and SD) patients, barzolvolimab, a humanized antibody that inhibits KIT activation by SCF, was well tolerated. Barzolvolimab demonstrated marked, rapid, durable depletion of skin MCs, circulating tryptase, reductions in clinical activity, and significant improvements in disease control and QoL. Barzolvolimab has potential as a therapy for MC‐mediated diseases.Abbreviations: CIndU, chronic inducible urticaria; ColdU, cold urticaria; FcR, Fc receptor; Ig, immunoglobulin; KIT, KIT proto‐oncogene, receptor tyrosine kinase; MC, mast cell; MRGPRX2, mas‐related G protein‐coupled receptor‐X2; QoL, quality of life; SCF, stem cell factor; SD, symptomatic dermographism